MOLECULAR CHARACTERISATION OF ANTIBIOTIC-RESISTANT BACTERIA FROM SELECTED WATER DISTRIBUTION SYSTEMS IN SOUTHWESTERN NIGERIA (2014)
The presence of Antibiotic-Resistant Bacteria (ARB) in water sources and treated drinking water is an emerging public health issue. Antibiotic resistance genes and mobile genetic elements (integron and gene cassettes) have been reported as bases of resistance in ARB. Available data on ARB in southwestern Nigeria are based on phenotypic studies. Information on molecular basis of resistance in ARB is necessary to determine the mode of resistance transfer among bacteria. This research was therefore aimed at molecular characterisation of ARB in water distribution systems of dams in Southwestern Nigeria. Ninety-six water samples were purposively collected aseptically into sterile screw cap bottles from six selected water distribution systems of dams in Ife, Ede, Asejire, Eleyele, Owena-Ondo and Owena-Idanre in Southwestern Nigeria. Samples were collected four times between December 2010 and July 2011 from raw, treated and two randomly selected municipal distribution taps. Bacteria were isolated from water samples and characterised using 16S rDNA sequencing. Antibiotic susceptibility of isolates was determined using point inoculation method. Multi-Drug Resistant (MDR) bacteria were selected based on resistance to over three classes of antibiotics and resistance genes were characterised by PCR and microarray analysis. Class 1 integron was detected by PCR while variable regions of integrase positive isolates were sequenced to identify inserted gene cassettes. Data were analysed using descriptive statistics and ANOVA at p=0.05. A total of 292 bacteria isolates were obtained. The highest (11.0%) bacteria occurrence was from Owena-Idanre raw water while the lowest (0.3%) was obtained from Eleyele treated water. They were identified as α-proteobacteria (4), β-proteobacteria (39), γ-proteobacteria (131), bacteroidetes (4), actinobacteria (2), firmicutes (105) and uncultured bacteria (7). Resistance to tetracycline, sulfamethoxazole, ampicillin and streptomycin among the 191 found to be MDR bacteria were 62.8, 93.7, 90.0 and 52.8 % respectively. Significant variation was observed between percentage of MDR bacteria in Owena-Idanre dam (12.6%) and those from Ife dam (4.2%). The most frequent resistance genes detected among MDR bacteria were ant(3’)b (56/101), blaTEM (59/172), sul 2 (51/179) and tetA (23/120). The highest incidence of ant(3’)b (12.5%) was found among bacteria obtained from Eleyele raw water while tetA (13.0%) was from Owena-Ondo treated water. Other antibiotic resistance genes such as floR, tetJ, tetH, StrB, qnrA1, dfrA21 and aadE from bacteria isolated in Asejire treated water and Owena-Idanre municipal taps were detected with Microarray. Class 1 integron was found in 42 bacteria with the highest frequency (14.3%) in Eleyele raw water while 2.4% each were obtained from Ede, Asejire and Eleyele municipal taps. Variable region was detected from 69.0% of bacteria carrying class 1 integron. Gene cassettes identified in the variable region of class 1 integron include aadA1, bla CTX-M, dfrA, Sul 1 and qnr A1 encoding resistance to aminoglycoside, extended β-lactams, trimethoprim, sulfamethoxazole and quinolones respectively. The presence of multi-drug resistant bacteria carrying different antibiotic resistance genes, integrons and gene cassettes as revealed by molecular characterisation, in the water distribution systems could facilitate the transfer of antibiotic resistance among bacteria of public health significance, hence the need for surveillance.